2016
DOI: 10.1007/s00259-016-3541-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic glucose metabolism in glioblastoma as a potential prognostic factor

Abstract: The total lesion glycolysis in hypoxia (hTLG) was hMTV × FDG SUVmean. The extent of resection (EOR) involving cytoreduction surgery was volumetric change based on planimetry methods using MRI. These factors were tested for correlation with patient prognosis. 4Results:All tumor lesions were FMISO-positive and FDG-positive. Univariate analysis indicated that hMTV, hTLG, and EOR were significantly correlated with PFS (p=0.007, p=0.04, and p=0.01, respectively) and that hMTV, hTLG, and EOR were also significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…HIF1α stimulates aerobic glycolysis by inducing the expression of glucose transporters (such as glucose transporter 1, GLUT1) and directly targeting enzymes that regulate glycolysis, such as hexokinase 2 (HK2), phosphoglycerate kinase 1 (PGK1), lactate dehydrogenase A (LDHA), monocarboxylate transporter 4, and pyruvate dehydrogenase lipoamide kinase isozyme 1 (PDK1) [12]. A number of studies have revealed the importance of this metabolic reprogramming in cancer cells [13-17]. …”
Section: Introductionmentioning
confidence: 99%
“…HIF1α stimulates aerobic glycolysis by inducing the expression of glucose transporters (such as glucose transporter 1, GLUT1) and directly targeting enzymes that regulate glycolysis, such as hexokinase 2 (HK2), phosphoglycerate kinase 1 (PGK1), lactate dehydrogenase A (LDHA), monocarboxylate transporter 4, and pyruvate dehydrogenase lipoamide kinase isozyme 1 (PDK1) [12]. A number of studies have revealed the importance of this metabolic reprogramming in cancer cells [13-17]. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, a combination of two radiotracers was used to define a metabolic tumor volume in hypoxia, with the latter expressed as the volume of 18 F-FDG / 18 F-fluoromisonidazole ( 18 F-FMISO) double-positive, and 18 F-FMISO used as a radiotracer of hypoxia. This metabolic tumor volume in hypoxia was a significant predictor of progression-free survival and overall survival in glioblastoma patients (105).…”
Section: Prognosticationmentioning
confidence: 99%
“…In addition to this technical multimodality and the concomitant efforts of using various radiopharmaceuticals to characterize multiple biological targets (61,105), currently used multiparametric imaging also integrates the development and applications of innovative methods of image processing and analysis (120). While common metrics such as standard uptake value (SUV) or BTV or TBR only partially describes the properties of pathological lesions, novel parameters such as shape and uptake heterogeneity may provide additional information on the biological profile associated with tumor aggressiveness or degree of response to specific treatment and, consequently, with prognosis (121).…”
Section: Future Perspectives: Novel Radiotracers and Multimodalitymentioning
confidence: 99%
“…c‐Myc directly induces the transcription of genes encoding glycolytic enzymes, including HK‐II, LDHA, PGK1 and GLUTs . Numerous studies have demonstrated the importance of this metabolic reprogramming in cancer cells . Moreover, it was reported that c‐Myc can be regulated by CaMK II to facilitate cancer cell proliferation …”
Section: Introductionmentioning
confidence: 99%